Profiles of lactate dehydrogenase, tartrate resistant acid phosphatase and alkaline photophatase in saliva during orthodontic treatment - Shahrul Hisham Zainal Ariffin,; Mohd Faiz Ellias,; Rohaya Megat Abdul Wahab,; Yosni Bakar,; Sahidan Senafi, (Universiti Kebangsaan Malaysia, 2010)
During orthodontic treatment, the progress of tooth movements can be classified into four stages, i.e. activation (related to tissue inflammation or cells’ death), resorption, reversal and restructuring of new bones. Tooth movement is related to metabolic changes around the mouth. The objective of this study was to determine enzymes profiles from patient’s saliva during orthodontic tooth movement, i.e., lactate dehydrogenase (LDH) for inflammation, tartrate resistant acid phosphatase (TRAP) for bone resorption and alkaline phosphatase (ALP) for bone formation. Saliva samples were collected from 6 orthodontic patients. Activities of all enzymes were measured before placement of orthodontic fixed appliances (normal activity) followed with day 3, 7, 10, 14, 17, 21, 24, 28 and 31 after the braces were activated. All enzymes (LDH, TRAP and ALP) showed significantly (p≤0.05) higher specific activities as compared to normal. LDH showed the increment at the early phase of treatment (day 3,7 and 10), TRAP at day 14 and 17 followed by ALP at day 17, 21 and 24. As a conclusion, the profiles of enzymes activities showed that inflammation occured during early phase of treatment followed by bone resorption and bone formation. In addition, the inflammations, resorption and bone formation phases in orthodontic treatment were found to be completed within 24 days.